Low-Cost Sensor Based on Internet of Things for PM₂¸₅ Air Quality Monitoring - Santoso, Dian Hudawan; Santosa, Sri Juari; Sekaranom, Andung Bayu (Indonesian Journal of Geography, 2025)
The issue of air pollution, particularly that of particulate matter (PM2.5), has recently garnered significant global attention. However, the implementation of effective air quality management is frequently impeded by a dearth of adequate monitoring and measurement equipment. In Yogyakarta City and its surrounding areas, monitoring ambient air concentration, particularly PM2.5, remains difficult due to the limitations of monitoring tools such as Air Quality Monitoring System (AQMS). These tools are costly to operate, which further worsens the challenges. Therefore, this research aimed to design Internet of Things (IoT)-based Low-Cost Sensor (LCS) as an economical and reliable alternative to PM2.5 monitoring tools. Research and Development method was used with Plomp development model, which included investigation, design, calibration, as well as implementation. The results showed that IoT-based LCS followed the SNI 9178: 2023 standard with precision (SD 0.659 µg/m³; CV 23.59%), bias (slope 0.94; intercept 0.65 µg/m³), linearity (R² = 0.9), and RMSE 1.43 µg/m³. Moreover, the regression relationship between IoT-based LCS and AQMS was shown by the equation Y = 0.8633X + 2.7604, signifying a strong correlation between the two tools. During the analysis, IoT-based LCS appeared to be a promising solution for air quality monitoring, offering both effectiveness and affordability, with real-time data relevant to environmental management.. The IoT-based LCS has been designed simply, meets the calibration standards of SNI 9178:2023, and can be applied in suburban areas.